Evaluation of fine needle aspiration cytology in the diagnosis of soft tissue tumors and its correlation with histopathological findings - Chandrakar, Ramesh; Sharma, Riti; Gahine, Renuka; Bhawnani, Dhiraj (International Journal of Research in Medical Sciences, 2017)
Background: Fine Needle Aspiration Cytology (FNAC) is a useful, safe and cost effective tool that is used in the diagnosis of lesions in various organs. Even though the literature on FNAC of soft tissue masses is relatively scarce, a large amount of interest has developed in this area in the last few years due to the low cost of the procedure, low incidence of complications, feasibility and high therapeutic efficiency. So the present study was undertaken to study the nature of various soft tissue tumors by FNAC and to compare the cytological diagnosis with the results obtained by biopsy. Methods: All cases 713 (Prospective-217 and Retrospective 496) included in present series were taken up for study. Aspiration of soft tissue lesions were performed following the technique of Zajicek et al. Smear was prepared, stained and examined. Histopathological details were available in 140 cases. Data was compiled in MS excel and checked for its completeness, correctness and then it was analyzed. Results: Total number of 11,560 FNAC was done in six and half year’s period from 1st April 2003 to 30th September 2009. Out of the total 713 cases of soft tissue tumors, 71.25% were reported as benign and 28.75% as malignant. Soft tissue tumors were more common in males in comparison to females, with M: F-1.63:1. Accuracy of FNAC for benign and malignant soft tissue tumours was 88.1% and 92.9% respectively. Conclusion: The overall diagnostic accuracy of FNAC in the present study was found 90%. FNAC is a safe and reliable method of recognizing benign and malignant soft tissue tumors and in most instances histological sub typing is possible. Cytological diagnosis must be based on strict cytological criteria and well controlled ancillary techniques.